The Development of Quizziz Assisted Think-Talk-Write Approach Teaching Materials to Improve Students Problem Solving Skills on Social Arithmetic - Bahari, Abdul Ghofur; Setiawan, Wahyu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
The development of this research was driven by the low academic achievement of high school students in the field of social arithmetic. This study aims to develop teaching materials through a test-assisted think-speak-write approach to improve problem-solving skills. The type of research used is development research with the 4D development model (Define, Design, Develop, Dissemination). Research using this model is limited to stage 3 (define, design, develop) due to limited research time. The object of this study was students of class VII at Al-Fatih KBB integrated college with data analysis techniques using descriptive qualitative techniques. Data was collected and then analyzed using Microsoft Excel. Results shows that the feasibility of teaching materials can be seen from the results of the evaluator's assessment, small-scale tests and large-scale tests. At 91% and 95% in the "Very Decent" category. Thus the student response to teaching materials has developed with a percentage of 82% and 84% are in the "Very Realistic" category. The limitations encountered in the development of educational materials are supported by the quizizz application. Study time is limited and school facilities are very inadequate to carry out learning in the classroom. Learning by using teaching materials media assisted by the quizizz application can be used and can be developed by the teacher on ongoing basis with different materials and themes.